Sviluppo della competenza fonologica in italiano come lingua seconda/straniera - Zorman, Anja (Linguistica (Ljubljana), 2017)
In researching language courses and didactic materials for Italian as second or foreign language little attention is generally paid to the development of phonological competence and speaking ability. The present study involved 140 pupils of elementary schools with Slovene as language of instruction in the bilingual area on the Slovene Littoral where Italian is taught as a second language. The research investigated the impact of phonology teaching and the development of phonological awareness on auditory perception abilities. The findings show that programs for the development of discriminatory listening and phonological segmentation of linguistic input critically influence the pupils% ability of auditory perception, provided they are long-term, systematic, intensive, and carried out in a direct interaction with the speakers of the target language. Consequently, they enhance the development of listening comprehension and communicative competence in the target language.
Keywords: didaktika jezika; drugi jezik; fonologija; fonološka zmožnost; Italian; italijanščina; tuji jeziki